Petroleum extract of Farfarae Flos alleviates nasal symptoms by regulating the Th1-Th2 cytokine balance in a mouse model of Allergic Rhinitis - Wu, Yongyan (Int J Med Sci, 2021)
Farfarae Flos is a traditional Chinese medicine that has long been used to treat allergies. In this study, we aimed to investigate the effect of a petroleum extract of Farfarae Flos (PEFF) in a mouse model of allergic rhinitis (AR) and to explore the underlying molecular mechanisms of action. An animal model of AR was established by sensitization and challenge of BALB/c mice with ovalbumin (OVA). PEFF was administered intranasally and AR nasal symptoms were assessed on a semi-quantitative scale according to the frequencies of nose rubbing and sneezing and the degree of rhinorrhea. The mechanism of action of PEFF was evaluated by histological analysis of nasal mucosa architecture and inflammatory status; ELISA-based quantification of serum OVA-specific IgE, interferon-γ (IFN-γ), and interleukin-4 (IL-4) concentrations; and immunohistochemical and western blot analysis of T-bet and GATA3 protein expression in nasal mucosa and spleen tissues. The results showed intranasal administration of PEFF alleviated AR symptom scores and reduced both the infiltration of inflammatory cells and tissue damage in the nasal mucosa. PEFF significantly decreased serum concentrations of OVA-specific IgE (P<0.01) and IL-4 (P<0.05) and significantly increased IFN-γ (P<0.01). PEFF also upregulated the expression of T-bet protein (P<0.05) but downregulated GATA3 protein (P<0.05) in nasal mucosa and spleen tissues. In conclusion, PEFF effectively reduces AR nasal symptoms and serum IgE levels in a mouse model and may act by correcting the imbalance between Th1 and Th2 responses.